IMPLEMENTASI HASIL PENELITIAN IDENTIFIKASI FUNGI DALAM TAPE TALAS (COLOCASIA ESCULENTA) SEBAGAI SUMBER BELAJAR BERUPA MODUL PADA POKOK BAHASAN FUNGI TERHADAP KETERAMPILAN MENGINTERPRETASI DATA SISWA KELAS X SMA AL ISLAM 1 SURAKARTA TAHUN AJARAN 2011/2012 - Wulandari, Badrisyiyani Eko; Harlita, Harlita; Muzayyinah, Muzayyinah (Pendidikan Biologi, 2011)
ABSTRACT - This is an experimental research of which result is  implemented in the learning process of Biology subject in the Xth grade of senior high school. The objectives of this research are: (1) to find out kinds of fungal in  taro tape (Colocasia esculenta) according to their morphological characteristics, (2) to  find out the effect of the utilization of the research result of  identification  as a modul-based  learning source towards  the interpreting data skill  of the Xth grade  of SMA Al Islam 1 Surakarta Academic Year 2011/2012. The implementation of the research result towards biology learning process in the Xth grade of senior high school was a quasi-experimental research.  The independent variable in this research is the modul-based learning source whereas the dependent variable  is  the interpreting data skill.  The population of the  fungal identification in taro tape (colocasia esculenta) was all  the  fungal in taro tape. The population of the implementation of the research result towards the learning process of  fungal  chapter was  all of the students of the Xth  grade of  SMA Al Islam 1 Surakarta  Academic Year  2011/2012.  The sample of the implementation of the research result towards the learning process of  fungal  chapter of Biology subject consisted of two classes, i.e. control and experiment class. The sampling method used cluster random sampling. The data collecting technique of  fungal identification research was experimentation and documentation whereas the implementation of the research result towards the interpreting data skill used observation methods. The test of the hypothesis for  the implementation of the research result towards the learning process of biology used t-test. From the research, it can be concluded that (1) there are two kind  genus of fungal in taro tape, i.e. genus Saccharomyces dan genus Aspergillus which identified according to their morphological characteristics, (2) the utilization of the research result of fungal identification in taro tape (colocasia esculenta) a modul-based learning source has a tangible  impact towards the  interpreting data skill  of the xth  grade  of SMA Al Islam 1 Surakarta Academic Year 2011/2012. Keywords: fungal identification, learning source, interpreting data skill